Inhibitory effects of four different kinds of triazole fungicides against Fusarium oxysporum f. sp. cubense and their differences - XIANG Dandan; YANG Xiaofang; YI Ganjun; TAO Haiqing; CHU Yuanqi; LI Chunyu (浙江大学学报. 农业与生命科学版)
The Chinese banana industry is under grave threat by Fusarium wilt of banana caused by Fusarium oxysporum f. sp. cubense (Foc). However, it is still obscure how to control this devastating disease effectively. In this study, the fungicidal activities of four triazole fungicides were tested by hyphae growth rates of Foc tropical race 4 (Foc TR4). The results showed that the fungicidal activities of these four fungicides were prothioconazole＞tebuconazole＞propiconazole＞myclobutanil. The morphology changes and membrane integrity of Foc TR4 in response to these four fungicides were evaluated by morphological observation of hyphae, and detection of relative conductivity and malondialdehyde (MDA) concentrations. Compared with the control group, all these four fungicides can cause abnormalities including increased hyphae branching, irregular distorted, shrivelled, sunken and flattened in hypha cells of Foc TR4. The MDA concentrations and membrane permeability of hypha cells were significantly elevated in all treatment groups. The activities of the cytochrome P450 enzymes were increased significantly so were the expression levels of cytochrome P450 sterol 14α-demethylase (CYP51) genes CYP51-1 and CYP51-3 upon treatment with these fungicides. Molecular docking and surface plasmon resonance (SPR) assays were employed to demonstrate interaction modes of four fungicides with CYP51 of Foc TR4. Even though prothioconazole showed less binding affinity with CYP51 than other three fungicides, it showed the strongest fungicidal activity against Foc TR4, which indicated the specificity of its mode of interaction with CYP51. This study can provide some theoretical references for the screening and rational design of novel fungicides for controlling Fusarium wilt of banana pathogen of Foc.